Examining supply chain agility using social network analysis : a thesis presented in partial fulfilment of the requirement for the degree of Master of Supply Chain Management at Massey University, Auckland, New Zealand - Le, Nguyen Hong Ngoc (Massey University, 2020)
In the current literature of supply chain agility (SCA), the extant agility models are not only rare but are also usually developed from the viewpoint of a firm rather than from a network perspective. While social network analysis (SNA) has proven its power and capacity in the social sciences, it has been rarely applied to supply chain management (SCM) phenomena. As such, this is a primary motivation for this study to take shape. The main focus of the research is refined to build on the Scion project on Rural Value Chains. It seeks to explore the appropriateness of SNA to assess SCA and to simultaneously make a relative agility comparison between supply chains by SNA. The empirical data are collected by structured interviews in a rural area of New Zealand and then analysed as a network case by varying SNA metrics, tools, and techniques. This thesis sheds light on how SNA is appropriate to tap into the areas that are barely recognised by the extant approaches. The findings show that SNA is well able to consider interactions and linkages in complex networks, and it also enables the integrated lens of network and complex adaptive system (CAS) to examine network agility in a comprehensive and systematic manner. SNA lends itself well to phenomena that directly relates to, or results from, network topology, connectivity, and interconnectedness, such as network visibility, speed of responses, and the ability to have multiple connection options. However, if used exclusively, SNA is less appropriate to examine attributes that either have qualitative elements or which are associated with firm operations. This thesis has added to the literature the applicability of SNA to evaluate SCA and to model SCs. For policy makers, it offers a clearer understanding of the local network for regional development plans. For business owners, it proposes an alternative approach of evaluating SCA, SC relationships, and SC members, so as to build up effective SCM strategies.
Keywords: 350909 Supply chains